The profile of the graduate in environmental engineering between the years 2012 and 2017: a case study in a University of the State of São Paulo - Santos, Arthur Pereira dos; Simionatto, Henzo Henrique; Américo-Pinheiro, Juliana Heloisa Pinê; Silva, Darllan Collins da Cunha e; Lourenço, Roberto Wagner (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The purpose of this work is to characterize the profile of the environmental engineer. To this end, a questionnaire was elaborated, containing 3 key questions, in addition to other questions about the academic and professional life of 220 graduates who graduated between 2012 and 2017 from a University located in the city of Sorocaba, São Paulo (SP). It was possible to observe a gradual growth in the number of environmental engineers trained per year, which may be related to the increase in the demand for courses that involve the environmental theme and the stimulation of public policies through funding and scholarships. However, it was noted that a large number of these professionals (25.8%) were unemployed, a fact that indicates a possible saturation of the labor market in the analyzed region. It was found that most of the graduates work as Environmental Analysts in private companies of the most diverse branches, a situation that is most likely related to the fact that more than 50% of the sampled engineers receive up to R$3,000.00. In addition, most of the environmental engineers were already inserted in the job market, as technicians, corroborating the situation of promotion through the federal government and the possible opportunities. Finally, it was found that most professionals believe that the profession of environmental engineer is new, and the multidisciplinarity in their training makes them a professional with a holistic and systemic view, in order to work together with other specialists. However, even so, they believe that it would be necessary to change the undergraduate curriculum.
Keywords: Environmental Engineer; Profession; Insertion in the labor market